The Choice of Strategic Alternatives Under Increasing Regulation in High Technology Companies - Birnbaum, Philip H. (Academy of Management Journal, 1984)
The strategic response of U.S. high technology companies in the medical X-ray manufacturing industry to increased governmental regulations from 1962 to 1977 is examined. Results suggest that regulations increase consumer and competitor uncertainty, with the consequence that firms select less risky strategies and decrease the riskier new product invention strategy. Larger firms reduce inventions less than smaller firms.